Pengaruh Faktor Pendidikan, Pengalaman Kerja, dan Pelatihan terhadap Pengetahuan Aparatur Pajak tentang Tax Avoidance (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Kebayoran Baru Tiga) - Hendra Permana; Nofryanti - (Universitas Pamulang, 2016)
The purpose of this research in to know the influence of education, work experience, and training on tax employee’s knowledge about tax avoidance. This research is using the primary data from questionnaire. This research is using survey method and regression analysis testing. Sample of this research is 60 from KPP Kebayoran Baru Tiga tax employees.Variables for this research are education, work experience, and training on tax employee’s knowledge about tax avoidance. The first step on the research is testing a reliability and validity of each variabel. And then the second step is regression testing of three variables on tax employee’s knowledge about tax avoidance. And the third step with a classic assumption test.Based on the results research shows that education influence significant on tax employee’s knowledge about tax avoidance. The results of the work experience no significant effect on tax employee’s knowledge about tax avoidance. Whereas training influence significant on tax employee’s knowledge about tax avoidance.